Molecular analysis of the gat genes from Escherichia coli and of their roles in galactitol transport and metabolism. - Nobelmann, B (1996)
In enteric bacteria, the hexitol galactitol (Gat) (formerly dulcitol) is taken up through enzyme II (II(Gat)) of the phosphoenolpyruvate-dependent phosphotransferase system (PTS), and accumulated as galactitol 1-phosphate (Gat1P). The gat genes involved in galactitol metabolism have been isolated from the wild-type isolate Escherichia coli EC3132 and cloned on a 7.8-kbp PstI DNA fragment. They comprise six complete open reading frames and one truncated open reading frame in the order gatYZABCDR'. The genes gatABC code for the proteins GatA (150 residues) and GatB (94 residues), which correspond to the hydrophilic domains IIA(Gat) and IIB(Gat), and GatC, which represents a membrane-bound transporter domain IIC(Gat) (35 kDa, 427 residues). The three polypeptides together constitute a II(Gat) of average size (671 residues). Gene gatD codes for a Gat1P-specific NAD-dependent dehydrogenase (38 kDa, 346 residues), gatZ codes for a protein (42 kDa, 378 residues) of unknown function, and gatY (31 kDa, 286 residues) codes for a D-tagatose-1,6-bisphosphate aldolase with similarity to other known ketose-bisphosphate aldolases. The truncated gatR' gene, whose product shows similarity to the glucitol repressor GutR, closely resembles a gatR gene fragment from E. coli K-12. The gat genes map in both organisms at similar positions, in E. coli K-12, where they are transcribed counterclockwise at precisely 46.7 min or 2,173 to 2,180 kbp. The genes are expressed constitutively in both strains, probably due to a mutation(s) in gatR. Transcription initiation sites for the gatYp and the gatRp promoters were determined by primer extension analysis.